Analisis Problematika Pelaksanaan Komponen Layanan Bimbingan dan Konseling - Muliadi Hasibuan, Marsal Yunas; Amelia, Tri Putri; Masril, Masril (Realita : Jurnal Bimbingan dan Konseling, 2022)
The background of this research is the lack of facilities and infrastructure for the implementation of guidance and counseling services so that it creates obstacles for students to get services from guidance and counseling teachers. The purpose of this study is that researchers want to examine in depth the problematic components of guidance and counseling services. This study used a descriptive qualitative method, with research subjects being guidance and counseling teachers. The techniques used to collect data in this study were observation and in-depth interviews. Data analysis uses the theory of Miless & Huberman, and test the validity of the data using triangulation. The results of the study found that first the lack of facilities and infrastructure became an obstacle for students to get responsive services in the form of individual counseling, students often felt uncomfortable and uncomfortable. Students also think that those who enter the BK room are people with problems. The second obstacle to the guidance and counseling service component is that there are counseling teachers who do not have an undergraduate counseling background, so they do not understand the implementation of guidance and counseling services. For the basic service component, individual planning and system support are going well, which is marked by students who are happy to get education, get more insight for career planning and have the confidence for further study. Collaboration between school stakeholders is going well for the advancement of guidance and counseling, namely supporting counseling teachers to continue further studies from bachelor to master's degree to support an increase in guidance and counseling teacher resources which have an impact on improving the quality of implementing guidance and counseling in schools.